Image advisor - Muslim women office wear / Edzuina Mohd Sharif - Mohd Sharif, Edzuina (Faculty of Computer and Mathematical Sciences, 2003)
Recommender system is a system that provides a recommendation, prediction or opinion that can assist the user in computerized solution. It is a new type of Internet technology since market trading nowadays migrated into e-commerce, which as a marketing tools to increase revenue. This technology had increased the competition among businesses. Thus, consumers are faced with too many choices without any guide or help for them to make decision. The fashion industry itself has now migrated to e-commerce where many fashion outlets offered on the Internet. One added value service to enhance customer relationship is by providing expert help in fashion consultation. Image Advisor - Muslim Women Office Wear expert system has been incorporated in the website to support fashion industry service. The system is to verify the suitable office wears for Muslim women in Malaysia. This system used Rule-based (RB) approach to achieve the objectives. Forward chaining (FC) and backward chaining (BC) are the two techniques that being used to get the result. The analysis and the comparison of office wear are based on Asian countries. Middle East countries and Western countries. From the knowledge acquisition, the information filtered and being classified, and the result used as information in the system to guide and give advice to the Muslim women about appropriate garment that follow Islamic dress requirements thus, project corporate image in the organization. A computational result, which is the most valuable from among the available solution, is presented.